(x+6)(x+5)=(x+2)(x-5)

Simple and best practice solution for (x+6)(x+5)=(x+2)(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+6)(x+5)=(x+2)(x-5) equation:



(x+6)(x+5)=(x+2)(x-5)
We move all terms to the left:
(x+6)(x+5)-((x+2)(x-5))=0
We multiply parentheses ..
(+x^2+5x+6x+30)-((x+2)(x-5))=0
We calculate terms in parentheses: -((x+2)(x-5)), so:
(x+2)(x-5)
We multiply parentheses ..
(+x^2-5x+2x-10)
We get rid of parentheses
x^2-5x+2x-10
We add all the numbers together, and all the variables
x^2-3x-10
Back to the equation:
-(x^2-3x-10)
We get rid of parentheses
x^2-x^2+5x+6x+3x+30+10=0
We add all the numbers together, and all the variables
14x+40=0
We move all terms containing x to the left, all other terms to the right
14x=-40
x=-40/14
x=-2+6/7

See similar equations:

| -5p-8=1+5p-9 | | x^2-((3/2)x)^2=4 | | 3x=131 | | x2=49/69 | | x2=49169 | | 13(17x-23)^2=156 | | 25+12x=6x+4 | | 21=-6x | | -3-4(7-4x)=81 | | 4+13(17x-23)^2=160 | | 5m-58=0 | | 4(v-4)=-5v-25 | | 7u+39=3(u+9) | | -6u-6=-3u+15 | | -8=~3+m/3 | | 8n−8=60 | | 5x+11=35-7x | | 3+6(n+8)=93 | | 12=2l+1 | | D=9/4(m-35) | | -100=-6(-2r+4)-4 | | -6u-6=3(u+5) | | |4a+11|=-2a | | 17=(x-1)-(x-6) | | -1=z/3-3 | | Y=8(2+x) | | -6u-6=3u+15 | | -28-4p=-4p-7(-4-4p) | | -8(b-97)=8 | | -4(1+2b)=-20-4b | | x/3(x+1)=2(x-1) | | 695-8v)+12=-10 |

Equations solver categories